Factors associated with mental health status among the students living in girls’ hostel of Baneshwor, Kathmandu - Bhatta, Himani; Bhatt, Ashish (International Journal Of Community Medicine And Public Health, 2023)
Background: The purpose of this study was to identify factors associated with mental health status among students residing in girls’ hostels in Baneshwor, Kathmandu. Methods: From June 2022 to November 2022, a cross-sectional survey was carried out among 253 students residing in several girls’ hostels in the Baneshwor, Kathmandu. Face-to-face survey took place amongst them. Results: The study found that 67.2% (n=253), 84.6% (n=253), and 69.2% (n=253) of individuals have (mild/moderate/severe/extremely severe) depression, anxiety, and stress, respectively. Factors such as self-blame were linked to feelings of depression, anxiety, and stress. Other characteristics such as roommate disturbance, abuse, lack of assistance from others, homesickness, and a safe and supportive environment were all linked to one or both depression, anxiety, and stress. Other characteristics, such as the death of a family member in the previous two years and meal satisfaction, were not linked to DAS. Conclusions: Students in female hostels had greater levels of depression, anxiety, and stress. It is vital to assist and offer a necessary environment for female students living in hostels far from home in order to mitigate the severe toll that mental illness impose.